Effect of Ethanol Processing on Functional Properties and Composition of Peanut Proteins - ZHANG Xiang-feng; GUO Xing-feng; ZHANG Qian; ZHU Ting-wei; ZHAO Shu-chao; ZHANG Ming; LIN Feng-yan (Liang you shipin ke-ji)
The quality of peanut protein prepared under different ethanol processing conditions varies, leading to differences in protein properties and subsequently in the functional characteristics and applications of the protein products. Response surface methodology was employed to optimize the preparation conditions and analyze the functional properties of the peanut proteins. The protein optimized for product yield, designated as D1, was obtained under the conditions of 75.00% volume fraction, 35.00 ℃ extraction temperature, and 55.45 min extraction time, resulting in a product yield of 87.82% and a protein content of 58.02%. The protein optimized for protein content, designated as D2, was prepared with a 67.12% volume fraction, 42.02 ℃ extraction temperature, and 58.28 min extraction time, achieving a protein content of 61.10% and a product yield of 86.08%. Compared with control peanut (CP), the protein content of D1 and D2 increased by 5.72% and 8.80% respectively. Improvements were observed in foaming capacity, emulsifying properties, water and oil retention, and gel-forming abilities. The particle size of D1 and D2 protein products was reduced, while the contents of albumin and conarachin dissolved in water increased. Additionally, surface hydrophobicity increased, and interfacial tension decreased, leading to significant improvements in the functional properties of peanut proteins.